Effect of Humic Acid and Cascing Fertilizer Dosage on the Growth and Yield of Japan Spinach (Spinacia oleraceae L.) - Dewi, Kania Sari; Widodo, R Wahyono; Amalia, Lia (Institute of Computer Science (IOCS), 2022)
The experiment was carried out in the experimental garden or practice field belonging to the Lembang Development Agricultural Vocational School, West Bandung Regency which is at an altitude of 1100 m above sea level (ASL) with the Andisol soil order and is planned to be carried out from September to October 2022. The experimental method used was an experiment using a randomized block design (RBD) with a factorial pattern consisting of two treatment factors, namely the dose of humic acid including 4 (four) factor levels, namely a0 = 0, a1 = 3 kg ha-1, a2 = 6 kg ha-1, a3 = 9 kg ha-1 , a4 = 12 kg ha-1 and the dose of vermicompost organic fertilizer includes 4 (four) factor levels, namely k1=0 , k2 = 12.79 tons ha-1, which was repeated three times. Each treatment was placed in each repetition randomly (random). Each replicate was placed in plots (10 plots) with the same size of 1m x 2m spacing of 25 cm x 25 cm, and a population of 32 plants per plot. There was an interaction between the dose of humic acid and vermicompost fertilizer on the height of Japanese spinach plants aged 15 DAP and there was an optimum dose between the dose of humic acid and vermicompost fertilizer on the height of Japanese spinach plants, namely 6 kg. ha-1 and 12.79 tons.ha-1